Dzielimy się doświadczeniem Results after early haemofiltration for acute renal failure after cardiac surgery - Ehrlich, Marek; Garlicki, Mirosław; Świstowski, Jarosław; Łabuś, Krzysztof; Gołębiewski, Sewer M.; Rydzewski, Andrzej Z. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: Acute renal failure (ARF) remains a significant cause of mortality after cardiac surgery. Aim: The aim of this study was to present our data with continuous venovenous haemofiltration (CVVH) in patients with ARF. Methods: 1136 consecutive patients (pts) who underwent adult cardiac surgical procedures performed between January 2004 and June 2005 were audited. Out of these, 32 patients required CVVH due to acute renal failure. Mean age in this group was 69±10 years. There were 27 males and 5 females with an average Euroscore of 7±3.5. Mean ejection fraction was 51±10%. All patients were in New York Heart Association (NYHA) class II. Twelve patients had preoperative renal insufficiency. Indication for surgery was coronary artery disease (CAD) in 23 patients, ascending aortic aneurysm in 4 and the remaining 5 patients had valvular heart disease requiring valve replacement. Results: Hospital mortality in the 32 patients who developed ARF and required CVVH was 41% (13/32) with overall 1.1% mortality associated with ARF. Cause of death was multi-organ failure in ten patients, postoperative myocardial infarction in 2 patients and sepsis in one. Mean time between operation and initiation of CVVH was 1.2±0.2 days. Mean duration of CVVH was 4.32±1.8 days. Conclusion: Early and aggressive CVVH is associated with better than expected survival in severe ARF after cardiac operations.